A split and merge video cryptosystem technique based on dual hash functions and Lorenz system. (3rd February 2022) - Al-Hazaimeh, Obaida M.; Abu-Ein, Ashraf; Al-Smadi, Ma'moun; Al-Bsool, Monther H.
Chaos-based cryptosystems and their behaviour in cryptography attract many scientists' and researchers' attention in physics and computer science in recent decades. A new dynamic cryptosystem for video sequence based on the combination of chaotic Lorenz map and dual hash functions is proposed in this paper to improve the security level of the video applications. First, split up the video sequence into video frames and audio samples. Then, the initial conditions for both video and audio are generated using SHA-256 and MD5, respectively. Next, a higher dimensional Lorenz chaotic system is adopted to confuse and diffuse the audio samples and video frames components. Moreover, to improve the security level of the proposed cryptosystem against different types of cryptanalytic attacks, the concept of multi-key is employed. The security analysis is conducted and the results indicate that the presented cryptosystem satisfies the security requirements against various attacks and can be directly applied in the real life video applications.